Plant Anatomy A Concept-Based Approach to the Structure of Seed Plants - Crang, Richard (Springer International Publishing, 2018)
Intended as a text for upper-division undergraduates, graduate students and as a potential reference, this broad-scoped resource is extensive in its educational appeal by providing a new concept-based organization with end-of-chapter literature references, self-quizzes, and illustration interpretation. The concept-based, pedagogical approach, in contrast to the classic discipline-based approach, was specifically chosen to make the teaching and learning of plant anatomy more accessible for students. In addition, for instructors whose backgrounds may not primarily be plant anatomy, the features noted above are designed to provide sufficient reference material for organization and class presentation. This text is unique in the extensive use of over 1150 high-resolution color micrographs, color diagrams and scanning electron micrographs. Another feature is frequent side-boxes that highlight the relationship of plant anatomy to specialized investigations in plant molecular biology, classical investigations, functional activities, and research in forestry, environmental studies and genetics, as well as other fields. Each of the 19 richly-illustrated chapters has an abstract, a list of keywords, an introduction, a text body consisting of 10 to 20 concept-based sections, and a list of references and additional readings. At the end of each chapter, the instructor and student will find a section-by-section concept review, concept connections, concept assessment (10 multiple-choice questions), and concept applications. Answers to the assessment material are found in an appendix. An index and a glossary with over 700 defined terms complete the volume.